PROMOTING AND SUSTAINING LOCAL TOURISM INDUSTRY IN CAMANAVA AREA BY BUILDING DISASTER RESILIENT COMMUNITIES - Espiritu, Rogelio I.; Guevarra, Katherine C. (ITB Journal Publisher, LPPM ITB, 2015)
This paper aims to present the potential growth of local tourism industry in the cities of Caloocan, Malabon, Navotas and Valenzuela (CAMANAVA) despite the perennial problem of flooding and alarming rate of land subsidence in the area. The University of the East (UE), a private higher education institution in partnership with the local government units, non-government organizations, civil society groups, higher education institutions, and other stakeholders has initiated sustainable community development programs to reduce the vulnerability of marginalized communities by increasing their capacities.